KONSEP ZAKAT PRODUKTIF PERSPEKTIF SYEKH MUHAMMAD ARSYAD AL-BANJARI DALAM KITAB SABILAL MUHTADIN (Analisis Sejarah, Hermeneutika, dan Istinbath) - Muhammad Sauqi (Fakultas Ekonomi dan Bisnis IAI Darussalam Martapura, 2025)
This study aims to analyze the concept of productive zakat from the perspective of Syekh Muhammad Arsyad al-Banjarî, as outlined in his book Sabîl al-Muhtadîn, using historical, hermeneutical, and istinbath approaches. Zakat, as one of the five pillars of Islam, carries a significant social dimension that is crucial in addressing social inequalities and alleviating poverty. In his book, Syekh Muhammad Arsyad al-Banjarî develops the idea of zakat not only as a consumptive act but also as a productive one, where zakat is provided as capital for the poor and needy to improve their welfare. This research reveals that Syekh Muhammad Arsyad al-Banjarî's concept of productive zakat is highly relevant to the socio-economic conditions of the Banjar Sultanate and offers a guide that can be applied in contemporary times. Using a hermeneutical approach, this study identifies the meaning embedded in the text of Sabîl al-Muhtadîn and its relevance to the concept of productive zakat, which aims to empower the economic wellbeing of the community. The historical approach is also employed to examine the social and economic context during the time the book was written, while istinbath explores the application of zakat principles in contemporary settings. The findings of this study indicate that productive zakat not only helps improve individual economies but also has the potential to significantly reduce poverty, thus serving as a crucial instrument for economic development in the Muslim community.